Pembangunan Desa Industri Berorientasi Tepung Sebagai Satu Sistem Ditinjau dari Aspek Kelembagaan dan Komoditi - Siswadi, Efrain Patola & (Innofarm:Jurnal Inovasi Pertanian, 2010)
ABSTRACT The purpose of this research was to known : (1) response of each vertical subsystem if instructed to industrial countryside development orient flour as one system, (2) activities walk from each subsystem horizontal which can be made a arm rest to be developed to become industrial countryside orient flour as one system, (3) role of local government in industrial countryside development orient flour as one system, (4) local commodity which have cultivated in sustaining flour industry which there have and also to be develop, ( 5) possibility of developing commodity introduction in sustaining industrial countryside development orient flour. Data collecting of primary used technique of circumstantial interview (in depth interview) and have the character of opened (open interview), while data collecting of secondary by citing tables or data which available from source data. The results of this research show: (1) all element in vertical subsystem, it was KUD, Private/Industry, BUMN, and the College gave positive response if develop " industrial countryside orient flour as one system" in region 4 J, (2) in subsystem primary, secondary, and tertiary, have there is activity which walk which can became a arm rest to be developed to became industrial countryside orient flour as one system, (3) role of Local Government in " development of countryside of industry orient flour as one system", is specify elementary positioning of area in direction development of industrial countryside, and displace farm function, what is poured in the form of by law. Others, is provide infrastructure, aid of equipments and technological, and also capital, (4) there are two local commodity that is potential maize and cassava to be developed to utilize to sustain industry of tapioca there is and also industrial other; to be develop, (5) development of grist in region 4 J very possible, because grist had cultivated since year 2004 in Subdistrict of Jatiyoso, and its productivity can reach 4 t/ha. Keyword : industrial countryside, system, institute and commodity